First women : the grace and power of America's modern First Ladies - Brower, Kate Andersen (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2016)
Presents an intimate examination of the true influence of White House First Ladies from Jackie Kennedy to Michelle Obama, which draws on previously untapped and candid sources to document their stories.
Keywords: Presidents' spouses -- United States -- Biography; Presidents' spouses -- United States -- History -- 20th century; Presidents' spouses -- United States -- History -- 21st century; Presidents' spouses -- United States -- Biography; Presidents' spouses -- United States -- History